Avaliação de diferentes protocolos de aplicação da terapia fotodinâmica antimicrobiana (aPDT) no tratamento da periodontite induzida em ratos imunossuprimidos com droga quimioterápica: estudo histomorfométrico, imunoistoquímico, imunológico e microbiológico - Longo, Mariéllen [UNESP] (2015)
Objective: This study evaluated the influence of multiple sessions of Low Level Laser Therapy (LLLT), adjuvant to the scaling and root planing (SRP), and antimicrobial photodynamic therapy (aPDT), with or without the mechanical treatment of SRP, in the treatment of experimental periodontitis (EP) in rats treated with chemotherapy 5- fluorouracil (5-FU). Materials and methods: Two hundred and sixteen animals were subjected to induction of EP by ligature in mandibular first molar right and left. 7 days after the ligature was removed, the animals were randomly divided into 9 groups: EP (n=24) - no treatment; 5FU-EP (n=24) - systemically treated with 5-FU (60mg/kg and 40mg/kg); 5FU-EP-SRP (n=24) - systemically treated with 5-FU, with SRP; 5FU-EP-SRP-1LLLT (n= 24) - systemically treated with 5-FU, with SRP, followed by LLLT (single session) (660 nm, 0.035 W; 4.2 J, 120 seconds; 1.23 W/cm2); 5FU-EP-SRP-4LLLT (n= 24) - systemically treated with 5-FU, with SRP, followed by LLLT (0, 24, 48 and 72 hours); 5FU-EP-SRP-1aPDT (n=24) - systemically treated with 5-FU, with SRP, followed by one application of antimicrobial photodynamic therapy (aPDT) (LLLT + methylene blue); 5FU-EP-SRP-4aPDT (n=24) - systemically treated with 5-FU, with SRP followed by aPDT (0, 24, 48, 72 hours); 5FU-EP-1aPDT (n=24) - systemically treated with 5-FU followed by aPDT; 5FU-EP-4aPDT (n=24) - treated systemically with 5-FU, followed by treatment with aPDT (0, 24, 48, 72 hours). Eight animals in each group were euthanized at 7, 15 and 30 days after local treatment. The area of bone loss (BL) in the furcation region was analyzed histometrically, histologically and analysis of immunostaining patterns for RANKL, OPG, TRAP, PCNA and CASP-3-AT were performed. Quantity of cytokine was measured by ELISA for PGE2 and TNF-α and IL-6 were evaluated by kits multiplex assays. The prevalence...